Development of a novel strategy for the quantification of ultra-trace impurity elements in high-purity magnesium using inductively coupled plasma tandem mass spectrometry - Liang Fu; Guangsheng Huang; Yaobo Hu; Xianhua Chen; Jingfeng Wang; Fusheng Pan (Journal of Magnesium and Alloys)
High purity magnesium is not only an important basic raw material for semiconductor and electronics industries, but also a promising new generation of electrochemical energy storage materials and biomedical materials. Impurities in high-purity magnesium affect material properties, which has become the most critical factor restricting its application. However, accurate analysis of multiple ultra-trace impurity elements in high-purity magnesium is extremely challenging. In this paper, based on the synergistic effect of N2O/H2 reaction gas mixture to eliminate spectral interference of inductively coupled plasma tandem mass spectrometry (ICP-MS/MS), a new strategy for the quantification of 45 ultra-trace impurity elements in high-purity magnesium was proposed. The results indicated that the limits of detection (LOD) were in the range of 0.02–18.5 ng L−1; the LODs of the challenging non-metallic elements Si and S were 18.5 and 12.2 ng L−1, respectively; and the LODs of all the other analytes were less than 10 ng L−1. Even under hot plasma conditions, LODs of alkali metal elements were also less than 5 ng L−1. The spike recovery of each analyte was 93.6%–107%, and the relative standard deviation (RSD) was 3.2%–6.9%, respectively. At a 95% level of confidence, no significant differences were found between the results obtained under the optimal conditions for the analyte with the developed method and the measurement results of SF-ICP-MS. The developed method indicated low LOD, high sample throughput, and complete interference elimination, demonstrating a new avenue for the rapid determination of ultra-trace elements in high-purity magnesium.